Multiple nutritional phenotypes of fission yeast mutants defective in genes encoding essential mitochondrial proteins. Issue 4 (7th April 2021) - Uehara, Lisa; Saitoh, Shigeaki; Mori, Ayaka; Sajiki, Kenichi; Toyoda, Yusuke; Masuda, Fumie; Soejima, Saeko; Tahara, Yuria; Yanagida, Mitsuhiro
Abstract : Mitochondria are essential for regulation of cellular respiration, energy production, small molecule metabolism, anti-oxidation and cell ageing, among other things. While the mitochondrial genome contains a small number of protein-coding genes, the great majority of mitochondrial proteins are encoded by chromosomal genes. In the fission yeast Schizosaccharomyces pombe, 770 proteins encoded by chromosomal genes are located in mitochondria. Of these, 195 proteins, many of which are implicated in translation and transport, are absolutely essential for viability. We isolated and characterized eight temperature-sensitive ( ts ) strains with mutations in essential mitochondrial proteins. Interestingly, they are also sensitive to limited nutrition (glucose and/or nitrogen), producing low-glucose-sensitive and 'super-housekeeping' phenotypes. They fail to produce colonies under low-glucose conditions at the permissive temperature or lose cell viability under nitrogen starvation at the restrictive temperature. The majority of these ts mitochondrial mutations may cause defects of gene expression in the mitochondrial genome. mrp4 and mrp17 are defective in mitochondrial ribosomal proteins. ppr3 is defective in rRNA expression, and trz2 and vrs2 are defective in tRNA maturation. This study promises potentially large dividends because mitochondrial quiescent functions are vital for human brain and muscle, and also for longevity.